ASSOCIATION OF BODY MASS INDEX WITH DISEASE SEVERITY, PHENOTYPES AND CLINICAL PRESENTATION IN PATIENTS WITH BRONCHIECTASIS: Body mass index and bronchiectasis - Janković, Jelena; Bojic, Zlatan; Vukosavljevic, Dragan; Zecevic, Andrej (Medical Research, 2024)
Introduction/Aim: Bronchiectasis is a chronic respiratory condition characterized by permanent dilatation of the bronchi with chronic respiratory symptoms. Some studies found association between malnutrition and bronchiectasis. But there are no enough studies on the topic of obesity. The aim was to evaluate the association between BMI and phenotypes, endotypes, clinico-radiological presentation and severity.Methods: A retrospective study included 120 patients with bronchiectasis. The socio-epidemiological, clinical, radiographic and laboratory characteristics were compared using statistical analyses, depending on BMI.Results: The mean age was 61.3 ± 7.6 years. Underweight, normal, overweight, and obese accounted for 6.7%, 48.3%, 27.5%, and 17.5% of all patients. There was statistically significant differences in BACI score (p 0.01), normal sputum finding (p 0.03), lower hemoglobin level (p 0.02) in underweight group and eosinophil endotype in all groups except underweight (p 0.04). Mean BACI score had rising trend from overweight and obese patients to normal weight followed by underweight category. Chronical colonization of Haemophilus was dominant in underweight and Pseudomonas in overweight and obese. Asthma was most common in overweight and obese patients. We did not found differences between groups in spirometry finding, Reiff score and radiological phenotype.Conclusion: Underweight patients were females and younger than overweight patients, have lower lung function, systemic inflammation, higher BACI score, post-infective phenotype and predominantly normal sputum bacterial analysis for colonization screening. Opposite, overweight and obese had chronic colonization by P. aeruginosa, asthma comorbidity and eosinophil endotype. Those differences are very important for future specific treatment
Keywords: bronchiectasis; BMI; lung function; phenotype; endotype